Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1177/089124101030002002
|View full text |Cite
|
Sign up to set email alerts
|

Bisexuals at Midlife

Abstract: In the framework of a constructionist approach, a life-course point of view, and traditional concepts borrowed from identity theory, the authors report on a study of fifty-six San Francisco bisexuals. The data show that by midlife, changing life commitments among the participants were associated with a decrease in sexual involvement, a move toward sexual activity with just one sex, a decrease in contact with the bisexual subculture, and a decrease in the salience of a bisexual identity. Given these changes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Using data from a national population-based study in the USA, Bostwick et al (2010) found that men and women who identified as bisexual or engaged in bisexual behavior were at heightened risk compared with gay and straight peers for mood and anxiety disorders both over the past year and over the course of a lifetime. By midlife, bisexual adults also report a decrease in contact with the bisexual community and subculture (Weinberg, Williams, & Pryor, 2001). Thus, bisexuals may find themselves in a particularly vulnerable position for health as they not only are faced with the psychological stress of being a sexual minority, but also likely encounter greater health issues.…”
Section: Introductionmentioning
confidence: 99%
“…Using data from a national population-based study in the USA, Bostwick et al (2010) found that men and women who identified as bisexual or engaged in bisexual behavior were at heightened risk compared with gay and straight peers for mood and anxiety disorders both over the past year and over the course of a lifetime. By midlife, bisexual adults also report a decrease in contact with the bisexual community and subculture (Weinberg, Williams, & Pryor, 2001). Thus, bisexuals may find themselves in a particularly vulnerable position for health as they not only are faced with the psychological stress of being a sexual minority, but also likely encounter greater health issues.…”
Section: Introductionmentioning
confidence: 99%
“…In general, self-identified bisexual individuals also report high rates of bisexual behaviors (Dodge, Jeffries, & Sandfort, 2008;Stokes, McKirnan, & Burzette, 1993;Stokes, Vanable, & McKirnan, 1997). Longitudinal studies of bisexual individuals have demonstrated that bisexual identity remains stable for many self-identified bisexual individuals (Weinberg et al, 1994;Weinberg, Williams, & Pryor, 2001). However, fluidity and fluctuations in self-identity have also been found to occur often, particularly among women (Diamond & Butterworth, 2008;Diamond, 2003Diamond, , 2008.…”
Section: Little Public Health Research Has Explored Male Bisexuality mentioning
confidence: 95%